The clinical evidence for postbiotics as microbial therapeutics. (31st December 2022) - Mosca, Alexis; Abreu Y Abreu, Ana Teresa; Gwee, Kok Ann; Ianiro, Gianluca; Tack, Jan; Nguyen, Thi Viet Ha; Hill, Colin
ABSTRACT: An optimally operating microbiome supports protective, metabolic, and immune functions, but disruptions produce metabolites and toxins which can be involved in many conditions. Probiotics have the potential to manage these. However, their use in vulnerable people is linked to possible safety concerns and maintaining their viability is difficult. Interest in postbiotics is therefore increasing. Postbiotics contain inactivated microbial cells or cell components, thus are more stable and exert similar health benefits to probiotics. To review the evidence for the clinical benefits of postbiotics in highly prevalent conditions and consider future potential areas of benefit. There is growing evidence revealing the diverse clinical benefits of postbiotics in many prevalent conditions. Postbiotics could offer a novel therapeutic approach and may be a safer alternative to probiotics. Establishing interaction mechanisms between postbiotics and commensal microorganisms will improve the understanding of potential clinical benefits and may lead to targeted postbiotic therapy.